2022
DOI: 10.1155/2022/6857685
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Diagnostic and Prognostic Value of DACH1 Methylation in the Sensitivity of Esophageal Cancer to Radiotherapy

Abstract: To detect the methylation status of the cell fate determinant (DACH1) gene in esophageal cancer tissues and to explore the predictive value of methylation of DACH1 on the sensitivity to radiotherapy for esophageal cancer. Cancer tissues, corresponding paracancerous tissues, and 30 specimens of normal esophageal mucosal tissues from 70 patients admitted to the hospital after radical esophageal cancer radiotherapy from January 2016 to April 2017 were collected. The methylation status of DACH1 was detected by a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The DACH1 gene has been extensively studied and recognized as a crucial transcription regulator for the development of various organs and tissue, including the eyes, legs, nervous system, arterial vessels, and female reproductive tract in humans, mice, and Drosophila [ 52 , 53 , 54 , 55 , 75 , 76 , 77 ]. Furthermore, DACH1 has been recognized as a tumor suppressor gene in humans [ 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Despite its extensive study, limited research directly explored its role in hematopoiesis, with only two notable studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DACH1 gene has been extensively studied and recognized as a crucial transcription regulator for the development of various organs and tissue, including the eyes, legs, nervous system, arterial vessels, and female reproductive tract in humans, mice, and Drosophila [ 52 , 53 , 54 , 55 , 75 , 76 , 77 ]. Furthermore, DACH1 has been recognized as a tumor suppressor gene in humans [ 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Despite its extensive study, limited research directly explored its role in hematopoiesis, with only two notable studies.…”
Section: Discussionmentioning
confidence: 99%
“…Low expression of DACH1 has been observed in various types of tumors, such as breast tumors, esophageal cancer, lung cancer, and endometrial cancer. This low expression is correlated with increased tumor proliferation, metastasis, tumor mutation burden, reduced prognostic survival, radio sensitivity, and chemotherapy sensitivity [ 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Furthermore, high methylation of the DACH1 promoter results in reduced expression of DACH1 in tumors [ 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%